Hydroponic Development Training in Bukit Sari Village, Padang Tualang District as an Efficient Land Use Effort - Siregar, Putra Apriadi; Zulkarnain, Thahara Sumayya; Purnama, Tri Bayu (Universitas Islam Negeri Sumatera Utara, 2024)
Training is an effort to develop skills through experiential learning activities. Hydroponic-making training is one of the work programs implemented in field course groups (kuliah kerja nyata) activities. The training is aimed at the people of Bukit Sari Village so that the village community is educated and can use land efficiently by planting vegetables using a hydroponic system and hydroponic training using the demonstration method. The sequence of implementation begins with the preparation stage, the implementation stage, and the closing stage. Based on the training that has been carried out, it can be seen that there is an increase in the results of the pre-test and post-test regarding community knowledge about hydroponics; it is known that the average community pre-test result is 58.1 and the community post-test result is 85.4, with an average increase of 27.4. People who have been very enthusiastic and open to receiving hydroponic training support these findings, demonstrating increased public knowledge and understanding of hydroponics. Based on the implementation of hydroponic training that has been carried out, hydroponic training activities provide many benefits to the community, including being productive, creative, and innovative in utilizing land and time. The community can consume healthier vegetables, and besides that, the community can also increase the economic value of their own family and the village where they live